PAPR Reduction using Genetic Algorithm in OFDM System - Abdul Wahab, Aeizaal Azman; Husin, Hazmarini; Othman, Wan Amir Fuad Wajdi; Syed Hassan, Syed Sahal Nazli Alhady; Mohd Ramdan, Fatin Najwa (Applications of Modelling and Simulation, 2018)
Orthogonal frequency division multiplexing (OFDM) is a multicarrier modulation technique that relies on orthogonality feature to increase transmission data rate while enhancing spectral efficiency at the same time. OFDM’s major issue is the high peaks or peak-to-average power ratio (PAPR) that introduced due to summation of subcarriers’ signal. Many methods have been proposed to alleviate this issue, however, some may increase signal average power. In this paper, genetic algorithm (GA) technique is proposed for optimal solution in reducing PAPR of OFDM system. GA is a type of optimisation algorithm which is natural based selection and is used to find the optimal solution to the computational problem that maximises or minimises a particular function. The PAPR performance is compared and analysed based on the number of subcarriers and modulation size using complementary cumulative distribution function plots between the original OFDM and the proposed OFDM-GA method. By comparing with the original OFDM, simulation result demonstrates that the proposed method is able to reduce the PAPR around 50%.